Uji Daya Hambat Ekstrak Metanol Daun Ungu (Graptophillum pictum (L.) Griff) terhadap Pertumbuhan Bakteri Saluran Akar Gigi (Inhibition Test of Purple Leaf (Graptophillum pictum (L.) Griff) Methanol Extract toward Root Canal Bacteria's Growth) - Resti Ayu Indriana; Pudji Astuti; Atik Kurniawati (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background: Root canal bacteria in necrotizing pulp are dominated by polymicrobial bacterial colonization. Bacteria control were performed by using antribacterial irrigation. Purple leaf methanol extract contains triterpenoids, alkaloids, flavonoids, glycosides, saponins, and tanins which are to own antibacterial capability. Objective: To determine a wide range of consentrations, the minimal concentration of purple leaf methanol extract which able to inhibit the growth of root canal bacteria, and how much is the concentration of the purple leaf methanol extract which is equivalent to 2.6% sodium hypochlorite. Methods: The method was used well diffusion. Antibacterial test was indicated by the existance of the inhibition zone around the well hole. Total samples used were 56 samples for each 7 group treatment, which are concentration 100%, 50%, 25%, 12,5%, 6,25% of purple leaf methanol extract, 2.6% of sodium hypochlorite, and sterile water. The results of the study was then tested by the statistical parametric one way ANOVA and LSD. Results and Conclusion: The concentration of purple leaf methanol extract which ables to inhibit the growth of root canal bacteria is 12,5%, 25%, 50%, and 100% also the minimum concentration is 12,5%, and the concentration of purple leaf methanol extract which is equivalent to 2.6% of sodium hypochlorite is concentration of 25%.Keywords: Antibacterial, Root Canal Bacteria, Purple Leaf Methanol Extract, Graptophillum pictum (L.) Griff